2020
DOI: 10.3390/nu12020381
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Nutrients in the Modulation of Gut Microbiota: A Narrative Review

Abstract: Understanding how dietary nutrients modulate the gut microbiome is of great interest for the development of food products and eating patterns for combatting the global burden of non-communicable diseases. In this narrative review we assess scientific studies published from 2005 to 2019 that evaluated the effect of micro- and macro-nutrients on the composition of the gut microbiome using in vitro and in vivo models, and human clinical trials. The clinical evidence for micronutrients is less clear and generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
277
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(329 citation statements)
references
References 256 publications
(343 reference statements)
4
277
1
7
Order By: Relevance
“…In general, the group of gut microbes associated with a good health outcome are identified as “potential beneficial bacteria,” 33 such as short‐chain fatty acid (SCFA)‐producing bacteria ( Bacteroides, Faecalibacterium, Phascolarctobacterium, Roseburia, Bifidobacterium, Blautia, etc) 34‐36 . Those could potentially lead to development or progression of noncommunicable diseases are identified as “potential detrimental microbes,” 33 such as enteric pathogens and opportunistic pathogens ( Escherichia‐Shigella , Klebsiella , Enterococcus , Streptococcus , etc) 37‐39 …”
Section: Methodsmentioning
confidence: 99%
“…In general, the group of gut microbes associated with a good health outcome are identified as “potential beneficial bacteria,” 33 such as short‐chain fatty acid (SCFA)‐producing bacteria ( Bacteroides, Faecalibacterium, Phascolarctobacterium, Roseburia, Bifidobacterium, Blautia, etc) 34‐36 . Those could potentially lead to development or progression of noncommunicable diseases are identified as “potential detrimental microbes,” 33 such as enteric pathogens and opportunistic pathogens ( Escherichia‐Shigella , Klebsiella , Enterococcus , Streptococcus , etc) 37‐39 …”
Section: Methodsmentioning
confidence: 99%
“…With the consumption of trimethylamine-containing meat products, such as phosphatidylcholine, choline, and L-carnitine, the microbiota produces trimethylamine N-oxide (TMAO). This metabolite together with increased levels of L-carnitine, choline, and phosphatidylcholine are direct cardiovascular risk factors [127][128][129]. In addition, other nutrients in the diet can modulate intestinal microbes for cardiovascular disease.…”
Section: Diet Nutrients and Microbiota In Cardiovascular Diseasesmentioning
confidence: 99%
“…The diet is one of the main factors in uencing the microbiota and the cooccurrence patterns of the caecal bacterial community [1,3]. Speci cally, dietary fat intake can modulate gut microbiota [4,5]. It has been reported that some fatty acids (FA) and in particular medium-chain fatty acids (MCFA) act as bacteriostatic (growth inhibiting) or bactericidal (killing) molecules [6,7].…”
Section: Introductionmentioning
confidence: 99%